Dynamics of migration and phase selective localization of nanoclay in HNBR/ENR blends. Issue 41 (13th July 2016) - Ali, Zulfiqar; Le, Hai Hong; Iqbal, Javed; Hussain, Murid; Hussain, Hazrat; Mahmood, Nasir; Nawaz Khan, Ahmad; Radusch, HansJoachim
ABSTRACT: The phase specific selective localization and dynamics of migration of nanoclay in hydrogenated acrylonitrile butadiene rubber (HNBR)/epoxidized natural rubber (ENR) blend systems is investigated. The phase specific dispersion of clay particles is monitored through measuring the online measured electrical conductance (OMEC) during mixing by means of a sensor system installed inside the chamber of an internal mixer. The results of different characterization techniques, such as atomic force microscopy, transmission electron microscopy, and small angle X‐ray scattering have been used to understand and interpret the OMEC behaviors of nanoclay‐filled rubber compounds individually (HNBR and ENR) and their blend systems. The observed online conductance is ionic in nature that arises due to the release of surfactant molecules from the clay galleries. It is observed that the OMEC behavior depends mainly on two factors: the localization of nanoclay in specific phase of the blend system and on the gradual development of blend morphology. The OMEC behavior and the supported data from the microscopic methods, clearly reveal the migration of organoclay from the ENR to HNBR phase during the mixing process, particularly localizing near the interface of the blend. Further, the localization of organoclay is also evaluated by applying the surface tension measurements based model, which also predicts the favorable localization of organoclay in HNBR phase of the blend. The work clearly suggests the OMEC method to be a powerful online tool to monitor and control the nanoclay dispersion and localization in rubber based nanocomposites during the melt mixing process. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44074. Abstract :